2009
DOI: 10.1111/j.1464-5491.2009.02732.x
|View full text |Cite
|
Sign up to set email alerts
|

A Ubiquitous Chronic Disease Care system using cellular phones and the internet

Abstract: The novel UCDC system presented in this paper improved multiple metabolic parameters simultaneously in overweight patients with both Type 2 diabetes and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
207
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(212 citation statements)
references
References 28 publications
(38 reference statements)
2
207
1
2
Order By: Relevance
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the evidence for short-term mortality was graded as moderate, given that results were precise, direct, and had low risk of bias (Table 2). Table 7), 4,21,49,61,62,69,[72][73][74][75][76][77][78][79][80][81][82][83] showing no clear differences between groups in hypoglycemia. The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2).…”
Section: Safetymentioning
confidence: 99%
“…The strength of evidence was graded as low, given the inconsistency and imprecision of the results (Table 2). Most studies reported hypoglycemia as total hypoglycemic events [75][76][77] (N=5) or p a r t i c i p a n t s e x p e r i e n c i n g h y p o g l y c e m i a ( N = 8). 61,62,69,73,74,78,80,82 Hypoglycemic outcomes were defined heterogeneously, with some studies based on self report 4,21,62,72,73,77,82 and others on glucose readings.…”
Section: Safetymentioning
confidence: 99%
“…age and BMI were 46 (±6) years and 32 (±3) kg m À2 , respectively. Of the 22 studies that provided the study-specific minimum BMI to define overweight or obesity, the value was X25 kg m À2 to o 30 kg m À2 except in three studies 26,35,38 that used a BMI o25 kg m À2 cut-off value for being overweight and three studies 28,32,36 that exclusively targeted participants with a BMI X30 kg m À2 . Most of the studies (17 studies) used an intent-to-treat analysis.…”
Section: Data Synthesismentioning
confidence: 99%
“…Table 2 shows details of the obesity treatment programs in each included study. To summarize the study-specific Webbased programs in terms of the role of the Internet, 16 studies [18][19][20][23][24][26][27][28][30][31][33][34][35][36][38][39] used the Internet as an adjunct to the non-Web-based obesity care support provided in both control and experimental groups. One study 25 used it as a substitute for face-to-face counseling.…”
Section: Data Synthesismentioning
confidence: 99%
“…The mean age of all participants ranged from 46 to 71 years. Ten studies (13,14,15,16,17,18,19,20,21,22) limited inclusion criteria to participants 1240 records identified through searches 899 records after duplicates removed 800 excluded based on abstracts.…”
Section: Study Characteristicsmentioning
confidence: 99%